Evaluasi Produktivitas Angkat Baja pada Bangunan Pabrik Kelapa Sawit - Silitonga, Desmon; Mardiaman, Mardiaman; Indriasari, Indriasari (Universitas Batanghari Jambi, 2025)
The growth of the industrial sector in Indonesia has driven the widespread use of steel structures due to their advantages in strength, construction speed, and cost efficiency. One significant application is in the construction of palm oil mills (PKS), which often face challenging site conditions requiring effective erection planning. However, steel structure erection productivity in PKS projects is frequently hindered by inappropriate work methods and unsystematic time recording. Significant variations in productivity across structural elements and the lack of comparative studies between crane and manual methods create a research gap that needs to be addressed. This study aims to evaluate and compare the productivity of steel structure erection in the Mill Building of a PKS project using crane and manual methods. A quantitative case study approach was applied at PT. Tunggal Yunus Estate, Tapung, Riau, with primary data collected through field observations, interviews, and project documentation. Productivity (kg/hour) was calculated based on the weight and installation duration of each structural element. The results show an average erection productivity of 480.98 kg/hour, with the highest productivity reaching 955.44 kg/hour for main columns and rafters using a crane. In contrast, manual methods for secondary elements such as wind bracing and canopy yielded the lowest productivity at 156.78 kg/hour. These findings confirm that crane methods are more effective for main structural elements, while the use of manual methods should be carefully adapted to site conditions to maintain time-cost efficiency.